Editorial Board - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
After hard and tedious efforts for several months, finally the first edition of JIFAM can be published : JIFAM, Volume 1, Issue 1, March 2019. The JIFAM team express their gratitude to every body who already help the first issue publication.